Study of the 30% Quota of Women's Representation Against the Number of Legislative Members of the People's Representative Council of the Republic of Indonesia - Anggriani, Jum; Indah Harlina; Annisa Rahma (Jurnal Smart Hukum (JSH), 2024)
This study examines the phenomenon of the 30% quota of women's representation in the Indonesian House of Representatives (DPR RI) legislative institution not being met even though affirmative policies have been implemented for almost two decades. Using a normative legal method supported by a legislative, conceptual, comparative, and historical approach, this study identifies various factors inhibiting women's representation. The results of the study show that women's representation in the Indonesian House of Representatives (DPR RI) still reached 20.52% in the 2019 Election, not meeting the 30% target. The identified structural obstacles include the subordination of women in politics, the practice of money politics, a gender-biased recruitment system, and a deficit in women's political-social capital. The study recommends a comprehensive strategy in the form of gender mainstreaming in policy, women's capacity building, gender-just legal reform, political culture transformation, and a multi-stakeholder approach. This study contributes to the development of studies on gender politics and women's political representation, while also providing input for policy makers to improve regulations on women's representation in the general election system.